Differential regulation by cyclic AMP of starvation protein synthesis in Escherichia coli. - Schultz, J E (1988)
Of the 30 carbon starvation proteins whose induction has been previously shown to be important for starvation survival of Escherichia coli, two-thirds were not induced in cya or crp deletion mutants of E. coli at the onset of carbon starvation. The rest were induced, although not necessarily with the same temporal pattern as exhibited in the wild type. The starvation proteins that were homologous to previously identified heat shock proteins belonged to the latter class and were hyperinduced in delta cya or delta crp mutants during starvation. Most of the cyclic AMP-dependent proteins were synthesized in the delta cya mutant if exogenous cyclic AMP was added at the onset of starvation. Furthermore, beta-galactosidase induction of several carbon starvation response gene fusions occurred only in a cya+ genetic background. Thus, two-thirds of the carbon starvation proteins of E. coli require cyclic AMP and its receptor protein for induction; the rest do not. The former class evidently has no role in starvation survival, since delta cya or delta crp mutants of either E. coli or Salmonella typhimurium survived starvation as well as their wild-type parents did. The latter class, therefore, is likely to have a direct role in starvation survival. This possibility is strengthened by the finding that nearly all of the cya- and crp-independent proteins were also induced during nitrogen starvation and, as shown previously, during phosphate starvation. Proteins whose synthesis is independent of cya- and crp control are referred to as Pex (postexponential).